2020
DOI: 10.1016/j.psyneuen.2019.104476
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment improves metabolic and behavioral health in the BTBR mouse model of autism

Abstract: BTBR T+ Itpr3tf/J (BTBR) mice are an Autism Spectrum Disorder (ASD)-like model that exhibit behavioral and physiological deficits similar to those observed in patients with ASD. While behavioral therapy is a first line of treatment in ASD patients, comparable non-pharmacological treatments are less explored in murine models. Here, we administer a bio-behavioral intervention for BTBR mice by way of environmental enrichment (EE) -an experimental housing paradigm previously shown to improve systemic metabolism, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 60 publications
4
26
3
Order By: Relevance
“…Data with AMN082 would suggest the use of mGluR7 receptor agonists for treating anxiety (Spooren et al, 2010;Cieślik et al, 2018). Anxiety level is significantly higher in VPA-injected and BTBR mice (Gao et al, 2019;Queen et al, 2020). In agreement with previous results, we found overexpression of mGluR7 alleviates their anxiety-like traits.…”
Section: Discussionsupporting
confidence: 91%
“…Data with AMN082 would suggest the use of mGluR7 receptor agonists for treating anxiety (Spooren et al, 2010;Cieślik et al, 2018). Anxiety level is significantly higher in VPA-injected and BTBR mice (Gao et al, 2019;Queen et al, 2020). In agreement with previous results, we found overexpression of mGluR7 alleviates their anxiety-like traits.…”
Section: Discussionsupporting
confidence: 91%
“…It is understood that in utero VPA exposure results in lowered cAMP activity and thus low levels of pCREB (Wu et al, 2017) and consequently may define the low levels of DCX and BDNF in the present study. The loss of DCX in rats treated chronically (upto 90 days) with stimulants (Simchon Tenenbaum et al, 2015) and BDNF in 8-9 week old BTBR mouse (Queen et al, 2020) has been associated with expression of hyperlocomotive traits. In the present study, animals in the VPA group showed the presence of hyperactivity as suggested by the data of number of line crossings and distance traveled.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the evidence, confirmed by several studies [ 19 ], showed that there is a real correspondence between the genetic alterations present in autistic subjects and those present in the animal models is fundamental. This made it possible to consider using this animal model for studies that did not focus solely on the psychological and behavioral components, extending the research to the organic and metabolic spheres [ 30 ]. According to these considerations, we performed an initial morphological and subsequent biological evaluation of small intestine samples.…”
Section: Introductionmentioning
confidence: 99%